Military support and transnational terrorism. Issue 5 (2nd September 2016) - Du Bois, Cind; Buts, Caroline
Abstract : Analysing the relationship between the provision of military support and the probability of becoming the target of a terrorist attack, this paper contributes to the literature on the causes of transnational terrorism. We find that deployment of military troops of country X in country Y increases the probability of a terrorist attack on citizens of country X by a terrorist group located in country Y. Exporting weapons to country Y seems to increase the probability of being attacked by the terrorists of this country Y as well. Deploying materials, however, does not seem to significantly influence the probability of attack. Including lagged values for our military support variables ensures that the causality direction is from military support to terrorist attacks. Moreover, these results indicate that while the effect of military deployment on the probability of attack lasts for more than 1 year, the effect is rather short-lived.